SUBSTRATES AND AUXINS ON ROOTING OF STEM CUTTINGS OF “ESPINHEIRA-SANTA” - LIMA, Daniela Macedo de; SILVA, Carmem Luisa da; RITTER, Marlice; BIASI, Luiz Antonio; ZANETTE, Flavio; ZUFFELLATO-RIBAS, Katia Christina (Scientia Agraria, 2008)
Espinheira-santa (Maytenus ilicifolia) is a medicinal plant whose leaves are used for gastric ulcers treatments. In spite of its commercial and medicinal significance, few works are published about nursery tree production and vegetative propagation techniques for this plant. This study was carried out to evaluate the rooting of semihardwwod and herbaceous stem cuttings of espinheira-santa by auxins application in two kinds of substrates. Semihardwood cuttings had a leaf and 1cm of stem while herbaceous cuttings consisting of 6 to 8 cm of length and had two leaves. Semihardwood cuttings were treated with naphtalene acetic acid (NAA 0, 1500, 3000 mg L-1) and herbaceous cuttings were treated with indol butiric acid (IBA 0, 250, 500, 1000 mg L-1) solution. Cuttings were planted in plastic tubes containing vermiculite or coir dust like substrate and maintained in a greenhouse condition. The higher rooting percentage of semihardwood cuttings was observed in control plants (12,50% and 6,25%), with root number average per cutting of 1,48 and 1,04 and root length average of 1,28 and 2,03 cm in vermiculite and coir dust substrate, respectively. Herbaceous cuttings rooting percentage in control cuttings was 16,00%, with root number average per cutting of 2,46 and root length average of 0,89 cm in vermiculite. Herbaceous cuttings from coir dust fiber did not present roots. The largest percentage of alive cuttings and lowest percentage of dead cuttings was verified for semihardwood cuttings while in herbaceous cuttings was observed the inverse. Both kind of stem cuttings of espinheira-santa do not response for the application of NAA and IBA.